Venting the Central Compartment of the Hip Prior to Distraction Minimizes Overall Hip Distraction Forces. Issue 7 (31st July 2020) - Dillon, O; Mortensen, Alex; Adeyemi, Temitope; Ohlsen, Suzanna; Maak, Travis; Aoki, Stephen
Objectives: Arthroscopic hip surgery requires application of ipsilateral lower extremity traction to achieve adequate joint distraction and hip central compartment access. Higher traction forces applied to the lower extremity allow greater hip joint distraction, improving the working space, in order minimize iatrogenic chondral and labral injury. However, greater traction forces have demonstrated a higher potential for iatrogenic traction related injuries. Controversy exists about the clinical relevance of procedural modifications, such as venting the hip, as a means of reducing the amount of traction force required to safely distract the hip joint. This study was designed to evaluate the difference between no venting versus venting the hip prior to application of traction on the overall amount of traction needed to distract the hip joint during hip arthroscopy. Methods: A total of 55 hips in 54 consecutive patients undergoing primary arthroscopic hip surgery were retrospectively reviewed. Prior to any instrumentation, interval fluoroscopic images of the operative hip joint were taken at 0, 25, 50, 75, and 100 pound-force (lb-f) (0, 11.3, 22.7, 34.0, and 45.4 kilogram-force (kg-f)) of applied traction. The hip was then taken off traction and the joint was vented using a standard hip access 14-gauge spinal needle and injected with 20 milliliters of air. Before any additional intervention, traction was again applied to the operative extremity and fluoroscopic images were obtained at the same traction force intervals. Joint displacement was measured at each traction force interval both before and after venting. Fluoroscopic images were scaled based on AP pelvis radiographs in order to obtain millimeteric joint space measurements. Results: The mean difference in hip joint displacement without venting and with venting was 0.29, 2.24, 4.06, 4.13, and 3.80mm at 25, 50, 75, and 100 lbs-f of traction, respectively. Paired samples t-testing demonstrated statistically significant increases in distraction distance (p<0.01) at all levels of traction (Table 1). Prior to venting, 0%, 7.3%, 27.8%, 44.0% of hips distracted at least 10 mm at 25, 50, 75, and 100 lbs-f of traction, respectively. After venting, 14.6%, 45.0%, 74.0%, 86% of hips distracted at least 10 mm at 25, 50, 75, and 100 lbs-f of traction, respectively (Figure 1). Conclusion: This study demonstrates that venting the hip prior to the application of traction significantly increases the amount of distraction distance achieved for a given traction force at multiple levels of traction. With venting of the hip, the percentage of hips achieving at least 10mm of distraction for 100lbsf almost doubled. These findings suggest venting the hip prior to application of traction could serve to reduce the maximal amount of traction required to safely instrument the hip arthroscopically. Table 1. Pre and post-venting distraction distances by amount of traction force Amount of Traction Pre-venting Mean Distraction Distance (mm) Post-venting Mean Distraction Distance (mm) Mean Pre- versus Post-venting Difference (mm) p-value 0 lb-f (0 kg-f) 4.61 4.90 0.29 0.003 25 lb-f (11.3 kg-f) 4.87 7.11 2.24 <0.001 50 lb-f (22.7 kg-f) 5.82 9.88 4.06 <0.001 75 lb-f (34.0 kg-f) 7.66 11.78 4.13 <0.001 100 lb-f (45.4 kg-f) 9.22 13.02 3.80 <0.001 Figure 1.